Electrical and Energy Systems Integration for Maritime Environment-Friendly Transportation - Andrea Vicenzutti (MDPI AG, 2021)
The policies against climate change require the reduction of greenhouse gas emissions of marine transportation. To reach the planned goals, the most promising approach is working both on ships improvement and ports redesign. The latter must enable the new green ships supply with sustainable electrical energy, by integrating shore connection systems, local renewables, and energy storage systems. In this paper, a methodology to obtain such an objective is proposed, capable of taking into account both ships’ and ports’ characteristics. The methodology workflow is explained through a case study, where two shore connection power sizes and two different operative approaches for recharging the ship onboard energy storage are considered. A discussion about the most suitable energy storage technologies is also provided. The case study shows how the methodology can be applied, as well as demonstrating that the port infrastructure has a direct effect on the ship environmental performance.